2000
DOI: 10.1076/0167-6830(200006)1921-pft067
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities and limits of minimal invasive lacrimal surgery

Abstract: Endoscopy of the lacrimal drainage system with miniaturized endoscopes has been possible since 1990 and permits the direct evaluation of the lacrimal drainage system. Additionally, attached instruments permit recanalization in cases of stenosis of the lacrimal drainage system. Both an Erbium-Yag Laser and a miniaturized drill are available, with which a stenosis of the lacrimal drainage system can be opened under endoscopic control. Favorable findings for endoscopic recanalization are stenoses in the area of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Regarding DE, three-port system with an external diameter of 1.1 mm and internal diameter of 0.7 to 0.9 mm can permit the additional simultaneous use of microdrills, laser probes, micropunches, and miniature balloons [ 6 ]. Microdrill dacryoplasty utilizes battery powered miniaturized motor drills of 0.3 mm diameter, which can be easily incorporated along with the DE [ 7 ]. Wang et al [ 8 ] also reported successful outcomes in 84.9% of their patients with nasolacrimal duct obstruction (NDO).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding DE, three-port system with an external diameter of 1.1 mm and internal diameter of 0.7 to 0.9 mm can permit the additional simultaneous use of microdrills, laser probes, micropunches, and miniature balloons [ 6 ]. Microdrill dacryoplasty utilizes battery powered miniaturized motor drills of 0.3 mm diameter, which can be easily incorporated along with the DE [ 7 ]. Wang et al [ 8 ] also reported successful outcomes in 84.9% of their patients with nasolacrimal duct obstruction (NDO).…”
Section: Resultsmentioning
confidence: 99%
“…ENDI operations are generally performed under local anesthesia and are one of the minimally invasive procedures for treating PANDO (Supplementary file, Video 1 ). As compared with DCR, ENDI has various advantages in terms of surgical time, facial surgical scars, bleeding, and downtime 3 , 4 , 11 , 17 , 18 , 23 , 24 , 34 , 38 . In addition, because of the minimal risk of bleeding, ENDI can also be performed in patients receiving systemic anticoagulation and antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, with the development of the dacryoendoscope and advances in the fiber-optic system, recanalization procedures have steadily evolved. Lacrimal recanalization surgery includes endoscopic-guided trephination DCR, dacryorhinotomy, microdrill dacryoplasty, laser dacryoplasty, and anterograde balloon dacryoplasty 3 10 . Silicone tube intubation and anterograde balloon dacryoplasty are commonly used for treating partial obstruction or stenosis of the lacrimal duct 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the advent of advanced endoscopy technologies allowed for a handful of minimally invasive operating techniques to emerge, posing alternative treatment options. Two of which in particular, namely laser-assisted dacryoplasty and microdrill dacryoplasty, have been shown to be viable first-step procedures in the treatment of short-segment membranous stenoses of the nasolacrimal duct [ 9 11 ]. Not only do these procedures take less time than external DCR, but also treated patients show shorter convalescence [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%